Do Political Finance Reforms Reduce Corruption?. Issue 2 (30th April 2021) - Hummel, Calla; Gerring, John; Burt, Thomas
Abstract: Reformers claim that public subsidies and regulation of political finance reduce corruption in politics, while observers worry that they have no impact on corruption, or even increase it. Despite national-level debates and billions of dollars spent, few studies have tested this relationship. The authors argue that political finance reform mitigates corruption by reducing private money's importance in politics and increasing the sanctions for corrupt behavior. Elite interviews from Paraguay's political finance reform illustrate the argument and elaborate the theoretical mechanisms. The study evaluates the argument using an original dataset measuring political subsidies from 175 countries from 1900–2015, as well as disaggregated corruption measures from the Varieties of Democracy project. The findings support the thesis that political finance reform reduces corruption, even in countries where such reforms are unevenly implemented.